2011
DOI: 10.1097/scs.0b013e3182074571
|View full text |Cite
|
Sign up to set email alerts
|

Photoelastic Stress Analysis of Different Designs of Cement-Retained Fixed Partial Dentures on Morse Taper Oral Implants

Abstract: There is no consensus in literature regarding the best plan for prosthetic rehabilitation with partial multiple adjacent implants to minimize stress generated in the bone-implant interface. The aim of this study was to evaluate the biomechanical behavior of cemented fixed partial dentures, splinted and nonsplinted, on Morse taper implants and with different types of coating material (ceramic and resin), using photoelastic stress analysis. A photoelastic model of an interposed edentulous space, missing a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
21

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 21 publications
2
4
0
21
Order By: Relevance
“…Stegaroiu et al 30 and Menani et al 31 concluded that the use of ceramic prostheses decreases the amount of stress transmitted to the implants. Thus, the use of ceramic materials would be beneficial for implant survival when taking into account transfer of stress, which confirms the findings of the present study that found that the transfer of force of Zr implants was lower than the stress transmitted by metal implants.…”
Section: Cylindersmentioning
confidence: 99%
“…Stegaroiu et al 30 and Menani et al 31 concluded that the use of ceramic prostheses decreases the amount of stress transmitted to the implants. Thus, the use of ceramic materials would be beneficial for implant survival when taking into account transfer of stress, which confirms the findings of the present study that found that the transfer of force of Zr implants was lower than the stress transmitted by metal implants.…”
Section: Cylindersmentioning
confidence: 99%
“…Baseado nesse pressuposto, Nissan et al (2010) Menani et al (2011) estudaram, pelo método da fotoelasticidade, o comportamento biomecânico de próteses parciais fixas cimentadas sobre implantes do tipo cone morse, variando o revestimento estético (resina e cerâmica) e a esplintagem das coroas (presente ou ausente). Foi utilizado um modelo fotoelástico contendo réplicas em resina de um 1º pré-molar e um 2º molar inferior, além de implantes substituindo o 2º pré-molar e o 1º molar.…”
Section: Biomecânica Das Próteses Implantossuportadasunclassified
“…Vários trabalhos têm buscado a melhor configuração protética para reabilitações sobre implantes, especialmente na tentativa de minimizar tensões excessivas transmitidas ao tecido ósseo adjacente (Guichet et al, 2002;Pierrisnard et al, 2003;Menani et al, 2011;Tiossi et al, 2012).…”
Section: Implantes Curtosunclassified
“…O conceito de que esplintagem das próteses implantossuportadas diminua as tensões ainda é incerto e pouco fundamentado em evidências bem conceituadas, e deve ser revisto, sendo que a relevância clínica dos variados achados na literatura ainda apontam para a necessidade de maiores estudos (Nissan et al, 2010 Alguns estudos têm explorado a variação do comprimento e diâmetro dos implantes, porém levando-se em conta situação ideal no tamanho da coroa e nivelamento ósseo (Huang et al, 2005;Bergkvist et al,2008;Nissan et al, 2010;Menani et al, 2011). Esses dois elementos são de fundamental importância no resultado final e prognóstico da reabilitação.…”
Section: Implantes Curtos X Esplintagem Ou Individualizaçãounclassified
“…Variados autores corroboram com a ideia que as próteses sobre implantes individualizadas apresentam distribuição de tensão menos uniforme em comparação às próteses esplintadas, mesmo quando submetidas a um ajuste oclusal bem balanceado (Skalak, 1983;Guichet et al, 2002;Wang et al, 2002;Menani et al, 2011). No presente estudo pode-se notar que as próteses sobre os implantes de comprimento regular não apresentaram tensões dissipadas no osso de forma significativamente diferente quando do uso de forma individualizada ou esplintada.…”
Section: Esplintagem E Individualização E Seus Efeitos No Tecido óSseunclassified